Reception and appropriation of international media in sub-Saharan Africa : the case of the Canal+ Group in Gabon - (:unkn) unknown (My University, 2023)
This research questions the media practices of the Canal+ group in Africa and in Gabon. Indeed, the arrival of Canal+ has been received as a cultural industry of entertainment and information that allows to get out of the media totalitarianism imposed by the rulers to the detriment of the aspirations and desires of the public. This is due to the absence of indigenous programmes that can compete with international media industries. The presence of Canal+ in Gabon is perhaps situated in the economist tradition of occupying a commercial space without competition. This strategy aims at reshaping the local media landscape through the diversification of its media contents with a view to putting down roots, while waiting for the birth of a consequent media rivalry. African countries thus appear to be fertile grounds for the consumption of international programmes at the economic level and, at the same time, they create cultural links between consumers, going as far as socialization. Analyzing the reception and appropriation of Canal+ programmes in Gabon, this work studies, through a sampling, the programmatic offer of Canal+ on this population. Thanks to the mechanisms of the survey, it reveals the formats and the transformed television agendas in the Gabonese television universe. This enabled us to base our questioning on the establishment of Canal+ in Gabon. Why Canal+ has conquered the media and cultural space of Gabonese viewers. Based on the system of internationalization of the media, this questioning examines in depth the management of local media and the dissatisfaction of viewers. This postulate is verified through the analyses resulting from the field studies that we carried out. Several interactions were involved in the interpretation of the data collected: observation, adaptation, field study and the competitive strategy of Canal+. The observation we made for this study is a participant observation. It highlights the logics that the Gabonese maint
Keywords: African Research